First record of the bryophilous fungi Paruephaedria heimerlii (Dactylosporaceae, Ascomycota) for Mexico - Guzmán-Guillermo, Jorge; Raymundo, Tania; Sorcia-Navarrete, Paola; Carvajal-Hernández, César Isidro (Instituto de Ecología, A.C., 2022)
Background and Aims: The briofilous fungi are a diverse and polyphyletic group of symbiotic mushrooms associated specifically with few bryophyte species, genera or families. Paruephaedria heimerlii stands out as a species with a bryophilous habit in Jungermanniales; it is known from Alaska, Europe, Japan and Tasmania. Therefore, the objective of this work is to present the first record of this species in Mexico, its first known tropical locality.Methods: The studied specimens were collected in the vegetation of pine-oak forest and tropical cloud forest in the state of Veracruz, Mexico. The material was herborized and decontaminated by cooling, followed by determination from histological sections of the ascomas and observed with an optical microscope. Finally, the material was deposited in the fungal collections of the herbaria ENCB of the Instituto Politécnico Nacional and XALU of the Facultad de Biología of the Universidad Veracruzana.Key results: Using morphological characteristics and measures of sexual structures like spores, asci and hymenial structures, the studied material was determined as Paruephaedria heimerlii, representing the first record of this species both in Mexico and for the tropics. Conclusions: According to our observations and comparisons with reports in literature, it is probable that the presence of P. heimerlii is not conditioned to the temperature or altitude of the habitat in which it is found, but to the availability of hosts.